International Rankings, Domestic Institutions, and Gender Policy: Comparative Evidence from Denmark and Uzbekistan (Texas Journal of Multidisciplinary Studies, 2026)
International rankings have become influential instruments of global governance, shaping state behavior through reputational pressure, benchmarking, and norm diffusion. Gender equality indices such as the Global Gender Gap Index and the Gender Inequality Index increasingly affect domestic policy agendas and international legitimacy strategies. This article examines how international gender rankings influence national gender policy in two structurally different states: Denmark and Uzbekistan. Using a qualitative comparative case study design grounded in governance by indicators and constructivist international relations theory, the article argues that rankings influence domestic gender policy through distinct mechanisms shaped by institutional context. In Denmark, rankings function primarily as instruments of policy reinforcement within an established gender equality regime. In Uzbekistan, they operate mainly as tools of international legitimation and external signaling within a transitional reform environment. The study demonstrates that the impact of rankings depends not only on external pressure but also on domestic institutional capacity and the presence of actors capable of translating indicators into sustained policy change. The findings contribute to debates on global governance and indicator-based governance